75.7k views
1 vote
Which quadratic equation is equivalent to (x^2-1)^2 -11(x^2-1)+24=0

A)u^2-11u+24=0 where u=(x^2-1)
B) (u^2)^2 -11(u^2) +24 where u = (x^2-1)
C)u^2+1-11u+24 =0 where u =(x^2-1)
D)(u^2-1)^2 -11(u^2-1) +24 where u =(x^2-1)​

2 Answers

6 votes

Answer:


\large\boxed{A)\ u^2-11u+24=0}

Explanation:


(x^2-1)^2 -11(x^2-1)+24=0\\\\\text{Substitute}\ (x^2-1)=u\\\\\underbrace{(x^2-1)}_(u)\ ^2 -11\underbrace{(x^2-1)}_(u)+24=0\to u^2-11u+24=0

User Almaz
by
5.7k points
3 votes

Answer: The correct option is

(A)
u^2-11u+24=0,~~\textup{where }u=(x^2-1).

Step-by-step explanation: We are given to select the correct quadratic equation that is equivalent to the following equation :


(x^2-1)^2-11(x^2-1)+24=0~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)

Let us consider that


u=x^2-1.

Substituting the value of u in equation (i), we get


(x^2-1)^2-11(x^2-1)+24=0\\\\\Rightarrow u^2-11u+24=0.

Thus, the required equivalent quadratic equation is


u^2-11u+24=0,~~\textup{where }u=(x^2-1).

Option (A) is CORRECT.

User Vijiy
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.